Rei Bantu’s journey - Sales Fonseca, Luiz Claudio Ribeiro (2024)
This paper seeks to analyze the musical and communicational aspects of the song Rei Bantu, more specifically from the re-recording by singer Jorge Du Peixe, released in 2021 as a single from the album Baião Granfino. Based on three axes of analysis: 1) taste performance and fandom disputes; 2) media and nostalgia; and 3) performance and expressive coherence, the aim is to investigate how Du Peixe's interpretation articulates and tensions dimensions such as modernity and tradition based on the following corpus: 1) the song per se; and 2) the single's launch post, published on the artist's social networks. The conclusion is that the work plays between different strands of taste, combining tradition and modernity by creating a place between these two ideal types.